MAXIMALISM AS A NEW DESIGN CONCEPT IN 21. CENTURY IN CONTEXT OF THE EFFECTS ON GRAPHIC DESIGN FIELD - Eker, Cihangir; Kizgindemir, Can (Anadolu Univ, 2022)
Maximalism is the name of the style that has started to find a place for itself in the art and design literature since the second half of the 20th century, which has a colorful, vibrant and rich structure in form. Maximalism, which was first seen in the field of fashion, began to inspire many designers, especially in the field of graphic design, for various reasons after the first decade of the 21st century, and at the same time became more desirable by customers. In this research, design movement maximalism will be examined. In this direction, the determined problem of the research is What are the reasons why Maximalism is being preferred in graphic design since the 21st century?. The purpose of the research is to express the reasons for the popularization of maximalism in the field of graphic design, and also to explain the features of the movement by identifying the common aspects of maximalism with other art and design trends that have inspired maximalism. The research is a qualitative study based on descriptive model. In order to form the conceptual framework in the research and discuss the research problem, a document review was carried out. The aim of the research is to clarify the concept of maximalism and to contribute to the graphic design literature.
Keywords: Maximalism; Graphic design; Postmodernism; Minimalism